Optimization of hybrid carbon–bamboo composite struc-ture based on flexural test and finite element simulation for UAV wing spar - Muhammad Nuzan Rizki; Asnawi Asnawi; Iqbal Kamar; Maulana Agil Ibrahim (Politeknik Negeri Lhokseumawe, 2026)
The structural performance of Unmanned Aerial Vehicle (UAV) wing spars demands a balance between high strength and adequate stiffness. This study investigates the optimal configuration of bamboo–carbon fiber hybrid composites and evaluates the suitability of different spar cross-section geometries through experimental flexural testing, Taguchi-based statistical optimization, and Finite Element Method (FEM) simulation. Nine composite variations were fabricated and tested in accordance with ASTM D7264, employing three control factors: volume fraction, fiber ratio, and stacking sequence. The experimental results indicated that variation V7 (60% total fiber volume, 40:60 bamboo–carbon ratio, CBC stacking sequence) demonstrates the highest mechanical performance, achieving a flexural strength of 288.5 MPa and a flexural modulus of 31.8 GPa, which was further supported by the highest Signal-to-Noise (S/N) ratios for both responses. The optimum material configuration was subsequently applied to FEM simulations of three spar cross-sectional geometries. The results revealed that the hollow circular profile exhibited a limited safety margin (SF = 1.09), whereas the W-shaped and hollow-square profiles achieved higher safety factors of 2.15 and 2.18, respectively. Among the evaluated designs, the hollow-square spar provides the most favorable structural response, characterized by lower maximum stress, reduced deflection, and the highest safety margin.